PENGARUH MENGGUNAKAN APLIKASI â€œHELLO ENGLISHâ€ TERHADAP PENGUCAPAN SISWA KELAS DELAPAN DI SMPN 1 SUMARORONG - Agustiana, Wanda; Batau, St. Haliah; Rampeng (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
The objective of the research was to know the influence of using Hello English application to enhance students’ achievement of pronunciation in English. This research applied pre-experimental in one class pre-test and post-test. This research conducted at SMPN 1 Sumarorong. In this research the population was the eight students of SMPN 1 Sumarorong in 2020/2021 academic year. The researcher used total sampling technique. The total sample was 30 students from class VIII-D. In analyzing the numerical data, the writer used SPSS v. 16.0. Based on the results of data analysis, the writer concluded that the use of Hello English application can increase students’ pronunciation skill, it’s proved by the mean score of the students in pretest and post-tes. The result of the research shows that Hello English application significantly increased students’ pronunciation ability after did treatment. The mean score improved from 42.33 in pre-test to 82.16 in post-test. It indicated that the one hypothesis (H1) was accepted and of course, the null hypothesis (H0) was rejected. It means that Hello English application could increase the students’ pronunciation ability in learning English at SMPN 1 Sumarorong.